Citational politics: Quantifying the influence of gender on citation in Digital Scholarship in the Humanities. (3rd August 2020) - Earhart, Amy E; Risam, Roopika; Bruno, Matthew
Abstract: Using citation analysis, we consider the role of gender in citation practices in conference special issues of Digital Scholarship in the Humanities . Our examination of citations in Digital Humanities conference special issues from 2006 to 2015 demonstrates gender bias in citational practices. This bias is consistent with broader trends in citational politics across the academy more broadly but is a threat to equity and justice within the scholarly community. We further offer proposals for improving citational practices to resist gender bias. Quantifying the impact of gender on citations, we argue, is one approach to understanding gender inequalities within digital humanities communities and to generating solutions to promote the broadest representation of digital humanities scholarship in scholarly communications.